Biaya Bangunan Baru Rumah Toko (Ruko) di Kota Jayapura Tahun 2023 - Santoso; Hamid Zulkarnain Rahakbauw; Akhyar Dhifi Reza Pratama Budi (Jurnal Penelitian Multidisiplin Ilmu, 2023)
As commercial buildings, shophouse buildings relatively dominate in Jayapura City with various variations in size. This variation in the size of shophouse buildings encourages the need to study the cost of new buildings. The main objective of this research is to analyze the amount of new shophouse building costs per square meter. This research uses descriptive statistical analysis tools, explaining the amount of new shop building costs per square meter, based on empirical data on the number of floors, area, and type of building material. Using 200 data of shophouse buildings in 2023, this research concludes that statistically, the cost of new shophouse buildings in Jayapura City in 2023 averages Rp5,081,333.00 per square meter (ceteris paribus). Statistically, the wider the shophouse building, the cheaper the new building cost per square meter (ceteris paribus).